2015
DOI: 10.1016/j.neuroimage.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific differences in fronto-parieto-occipital effective connectivity during short-term memory maintenance

Abstract: Although visual short-term memory (VSTM) performance has been hypothesized to rely on two distinct mechanisms, capacity and filtering, the two have not been dissociated using network-level causality measures. Here, we hypothesized that behavioral tasks challenging capacity or distraction filtering would both engage a common network of areas, namely dorsolateral prefrontal cortex (dlPFC), superior parietal lobule (SPL), and occipital cortex, but would do so according to dissociable patterns of effective connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our findings of a frontally-centered and a parietally-centered network involved in different aspects of WM-task performances are in line with recent ROI-based studies that have reported distinct functional roles of frontal and parietal regions on WM ( Kundu et al, 2015 ; Sarma et al, 2016 ; Li et al, 2017 ). The functional results from our estimated networks were also consistent with the voxel-wise results from our data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of a frontally-centered and a parietally-centered network involved in different aspects of WM-task performances are in line with recent ROI-based studies that have reported distinct functional roles of frontal and parietal regions on WM ( Kundu et al, 2015 ; Sarma et al, 2016 ; Li et al, 2017 ). The functional results from our estimated networks were also consistent with the voxel-wise results from our data.…”
Section: Discussionsupporting
confidence: 92%
“…Stimulating the right parietal cortex increased the amount of information maintained in the visual WM, whereas stimulating the right PFC improved focusing on relevant information and directing attention away from irrelevant stimuli ( Li et al, 2017 ). In addition, measuring the directed connectivity between the DLPFC and superior parietal lobule (SPL) during a visual WM task hinted toward a top-down drive from DLPFC to SPL that increased with WM load ( Kundu et al, 2015 ). These insights were based on a priori defined regions of interest (ROIs) and therefore described functional properties of separate brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported connections between these two cortices. Kundu et al ( 2015 ) found increased directed connectivity between the prefrontal and parietal areas during the “retention” process by using the Granger causality of the alpha oscillation; however, similar results were also observed between both the prefrontal and occipital areas, and the parietal and occipital areas during the “coding” process. In addition, Harding et al ( 2015 ) established a brain network model for cognitive control and WM, which included the inferior frontal junction, dorsolateral prefrontal cortex (DLPFC), pre-supplementary motor area, and intra-parietal sulcus, and analyzed the causality between different cortical regions via functional magnetic resonant imaging (fMRI).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, although the iIPS may play a role in both tasks, successfully performing the two tasks may require this region to exert its effects on other brain regions in different ways. For example, whereas activity in the alpha-band range may be linked to the role of spatial attention (e.g., Grimault et al, 2009), inhibition (e.g., Jensen & Mazaheri, 2010), or binding (Johnson et al, 2011) in VSTM, successfully perceiving an event may depend on long-range synchronization in the alpha and/or beta band between posterior parietal cortex and frontal and/or extrastriate regions (Kundu, Chang, Postle, & Van Veen, 2015; Gross et al, 2004). …”
Section: Discussionmentioning
confidence: 99%